Penguasaan Teknologi Informasi sebagai Pemoderasi Kecenderungan Wajib Pajak Menggunakan E-Filing - Bella Fadhilah Chusaeni; Rachmawati Meita Oktaviani (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2018)
Mastery of important information technology carried out by the taxpayer. Good technological mastery by the taxpayer will bring big benefits that are felt especially related to the time side. This study aims to analyze how much influence perceptions of usefulness, perceptions of ease to use, and mastery of information technology perceived by the taxpayer sourced by the Technology Acceptance Model developed by Davis 1993. This study is a quantitative study conducted by survey on respondents. Population in this research is all individual taxpayer in Semarang city. The number of respondents used as much as 120 respondents with sampling technique probability sampling. The result of the research shows the perception of usefulness, perception of ease to use and mastery of information technology partially affect the interest of the taxpayer to use e-filing. While the mastery of information technology can not moderate the relationship of perception of usefulness and perception of ease to use partially to the interest of using e-filing.